2019
DOI: 10.1093/cercor/bhz181
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integration of Neuronal Precursors in the Adult Murine Piriform Cortex

Abstract: The extent of functional maturation and integration of nonproliferative neuronal precursors, becoming neurons in the adult murine piriform cortex, is largely unexplored. We thus questioned whether precursors eventually become equivalent to neighboring principal neurons or whether they represent a novel functional network element. Adult brain neuronal precursors and immature neurons (complex cells) were labeled in transgenic mice (DCX-DsRed and DCX-CreERT2 /flox-EGFP), and their cell fate was characterized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 53 publications
2
68
0
1
Order By: Relevance
“…In contrast to DCX+ cells in the MOB, these cells are nonproliferative immature neurons of embryonic origin. 41 The pool of these cells decreases during aging due to continuous neuronal differentiation following new olfactory demands, 42 and we showed that this process is impaired in lean T2D rats. 22 Whether or not obesity-induced T2D affects these cells in the PC is unknown.…”
Section: Introductionmentioning
confidence: 67%
“…In contrast to DCX+ cells in the MOB, these cells are nonproliferative immature neurons of embryonic origin. 41 The pool of these cells decreases during aging due to continuous neuronal differentiation following new olfactory demands, 42 and we showed that this process is impaired in lean T2D rats. 22 Whether or not obesity-induced T2D affects these cells in the PC is unknown.…”
Section: Introductionmentioning
confidence: 67%
“…According to this view, AN in large-brained mammals would fall in the general rule of critical periods: temporal windows in which it is allowed, followed by the complete development of neural circuits (Semënov, 2019). It has been shown recently that mouse cINs can mature and be integrated into circuits at different ages (Benedetti et al, 2019), likely achieving a sort of "delayed neurogenesis." A recent report showing an abundance of INs in the sheep brain (Piumatti et al, 2018) supports the hypothesis that these cells might represent an evolutionary choice in large-brained mammals, as an alternative/parallel form of plasticity (Palazzo et al, 2018).…”
Section: Outcomementioning
confidence: 99%
“…The distribution and morphology of these cells are identical to those described previously by us and others in rats ( Bonfanti et al, 1992 ; Nacher et al, 2002 ). Most of the immature neurons in the adult rat PCX layer II have been generated during embryonic development ( Gómez-Climent et al, 2008 ) and progressively mature into functional excitatory neurons in this layer ( Rotheneichner et al, 2018 ; Benedetti et al, 2019 ), although the factors triggering or modulating these final steps of differentiation are still far from being understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, many studies have been conducted to characterize a population of immature neurons, which is densely distributed in the layer II of the adult rodent piriform cortex (PCX). Most, if not all, of these immature neurons are postmitotic cells generated during embryonic development ( Castillo-Gómez et al, 2008 ; Rubio et al, 2016 ), which progressively mature into typical excitatory neurons of the PCX ( Rotheneichner et al, 2018 ; Benedetti et al, 2019 ). These immature neurons transiently express the polysialylated form of the neural cell adhesion molecule (PSA-NCAM) ( Seki and Arai, 1991 ; Bonfanti et al, 1992 ), a plasticity molecule involved in different neurodevelopmental processes, such as neuronal migration, neurite extension, or synaptogenesis ( Rutishauser, 2008 ; Hildebrandt and Dityatev, 2013 ), which may also act as an insulating agent on these cells, preventing or limiting the formation of synaptic contacts ( Gómez-Climent et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%